Non-aqueous electrolyte secondary battery

JP7668828B2Active Publication Date: 2025-04-25PRIME PLANET ENERGY & SOLUTIONS INC
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2023003658
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2023-01-13
Publication Date
2025-04-25
Estimated Expiration
2043-01-13

AI Technical Summary

Technical Problem

The use of carbon nanotubes (CNTs) with a high G/D ratio in non-aqueous electrolyte secondary batteries is associated with high carbon dioxide emissions during production, and these CNTs with low G/D ratio exhibit poor storage properties and reduced output.

Method used

A non-aqueous electrolyte secondary battery design utilizing CNTs with a G/D ratio of 1.0 to 3.5, containing a Co component in the range of 5 to 120 ppm, and incorporating an additive that is a Li salt with a fluorosulfonyl or difluorophosphonyl group to enhance conductivity and suppress Co elution, thereby improving output and storage characteristics.

Benefits of technology

The battery achieves excellent output characteristics and storage properties while minimizing carbon dioxide emissions by using CNTs with a low G/D ratio and an optimized additive, effectively addressing the issues of low crystallinity and impurities.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 00000016_0000
    Figure 00000016_0000
  • Figure 00000017_0000
    Figure 00000017_0000
Patent Text Reader

Abstract

To provide a nonaqueous electrolyte secondary battery having excellent output characteristics and storage characteristics while using, as a conductive material, carbon nanotubes that are low in G / D ratio.SOLUTION: A nonaqueous electrolyte secondary battery disclosed herein includes a positive electrode, a negative electrode, and a nonaqueous electrolyte. The positive electrode includes a positive electrode current collector and a positive electrode active material layer. The positive electrode active material layer contains a positive electrode active material and carbon nanotubes. The carbon nanotubes contain a Co component. The carbon nanotubes have a G / D ratio of 1.0 to 3.5, the G / D ratio determined by Raman spectroscopic analysis. The amount of the Co component in the carbon nanotubes in the positive electrode active material layer is 5 mass ppm to 120 mass ppm. The nonaqueous electrolyte contains an additive that is a Li salt including at least one of a fluorosulfonyl group and a difluorophosphonyl group.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a non-aqueous electrolyte secondary battery. [Background technology]

[0002] 2. Description of the Related Art In recent years, non-aqueous electrolyte secondary batteries such as lithium ion secondary batteries have been suitably used as portable power sources for personal computers, mobile terminals, and the like, and as power sources for driving vehicles such as electric vehicles (BEVs), hybrid electric vehicles (HEVs), and plug-in hybrid electric vehicles (PHEVs), among others.

[0003] Due to the high electrical conductivity of carbon nanotubes (CNTs), a technique is known in which CNTs are used as a conductive material for electrodes of non-aqueous electrolyte secondary batteries (see, for example, Patent Document 1). Since a higher G / D ratio of CNTs determined by Raman spectroscopy indicates higher crystallinity and fewer impurities, CNTs with a high G / D ratio are preferably used for this conductive material. For example, Patent Document 1 uses CNTs with a G / D ratio of 50 or more.

[0004] Generally, CNTs are industrially produced by chemical vapor deposition (CVD), which uses a metal catalyst (e.g., Co, Fe, etc.) supported on a carrier (e.g., silica, zeolite, etc.) (see, for example, Patent Document 2). Patent Document 1 describes that metal catalysts may remain in CNTs used as conductive materials, and Patent Document 2 describes that the amount of remaining metal catalysts can be reduced by calcination and acid treatment. The smaller the amount of remaining metal catalyst, the higher the G / D ratio of the CNTs. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] International Publication No. 2017 / 199884 [Patent Document 2] JP 2005-272261 A Summary of the Invention [Problem to be solved by the invention]

[0006] On the other hand, in recent years, there has been a great demand for reducing carbon dioxide emissions. When sintering is performed to manufacture CNTs with a high G / D ratio, the amount of carbon dioxide emissions becomes very large. As a result of intensive research by the present inventors, it has been found that when CNTs that have not been sintered in order to reduce carbon dioxide emissions, i.e., CNTs with a low G / D ratio, are used as the conductive material of a non-aqueous electrolyte secondary battery, there is a problem that the storage characteristics are poor. In addition, it has been found that when the G / D ratio of CNTs is low, there is a problem that the output may be low.

[0007] Therefore, an object of the present invention is to provide a non-aqueous electrolyte secondary battery that uses CNTs with a low G / D ratio as a conductive material and yet has excellent output characteristics and storage characteristics. [Means for solving the problem]

[0008] The non-aqueous electrolyte secondary battery disclosed herein comprises a positive electrode, a negative electrode, and a non-aqueous electrolyte. The positive electrode comprises a positive electrode current collector and a positive electrode active material layer. The positive electrode active material layer contains a positive electrode active material and carbon nanotubes. The carbon nanotubes contain a Co component. The G / D ratio of the carbon nanotubes determined by Raman spectroscopic analysis is 1.0 to 3.5. The amount of Co component of the carbon nanotubes in the positive electrode active material layer is 5 ppm by mass to 120 ppm by mass. The non-aqueous electrolyte contains an additive which is a Li salt containing at least one of a fluorosulfonyl group and a difluorophosphonyl group.

[0009] According to this configuration, it is possible to provide a nonaqueous electrolyte secondary battery that has excellent output characteristics and storage characteristics while using CNTs with a low G / D ratio as the conductive material. [Brief description of the drawings]

[0010] [Figure 1]1 is a cross-sectional view showing a schematic internal structure of a lithium-ion secondary battery according to one embodiment of the present invention. [Diagram 2] FIG. 1 is a schematic exploded view showing the configuration of a wound electrode body of a lithium ion secondary battery according to one embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] Hereinafter, an embodiment of the present invention will be described with reference to the drawings. Matters not mentioned in this specification but necessary for carrying out the present invention can be understood as design matters for a person skilled in the art based on the prior art in the relevant field. The present invention can be carried out based on the contents disclosed in this specification and the technical common sense in the relevant field. In addition, in the following drawings, members and parts having the same function are described with the same reference numerals. Furthermore, the dimensional relationships (length, width, thickness, etc.) in each drawing do not reflect the actual dimensional relationships. In addition, the numerical range expressed as "A to B" in this specification includes A and B.

[0012] In this specification, the term "secondary battery" refers to an electricity storage device that can be repeatedly charged and discharged. In addition, in this specification, the term "lithium ion secondary battery" refers to a secondary battery that uses lithium ions as a charge carrier and realizes charging and discharging by the transfer of charge associated with the lithium ions between the positive and negative electrodes.

[0013] Hereinafter, the present invention will be described in detail using as an example a flat rectangular lithium ion secondary battery having a flat wound electrode body and a flat battery case, but it is not intended that the present invention be limited to the embodiment described therein.

[0014] The lithium ion secondary battery 100 shown in FIG. 1 is a sealed battery constructed by housing a flat wound electrode body 20 and a nonaqueous electrolyte 80 in a flat rectangular battery case (i.e., an outer container) 30. The battery case 30 is provided with a positive electrode terminal 42 and a negative electrode terminal 44 for external connection, and a thin-walled safety valve 36 that is set to release the internal pressure when the internal pressure of the battery case 30 rises to a predetermined level or higher. The battery case 30 is also provided with an injection port (not shown) for injecting the nonaqueous electrolyte 80. The positive electrode terminal 42 is electrically connected to the positive electrode current collector plate 42a. The negative electrode terminal 44 is electrically connected to the negative electrode current collector plate 44a. The material of the battery case 30 is, for example, a lightweight metal material with good thermal conductivity, such as aluminum. Note that FIG. 1 does not accurately represent the amount of the nonaqueous electrolyte 80.

[0015] 1 and 2, the wound electrode body 20 has a configuration in which a positive electrode sheet 50 and a negative electrode sheet 60 are overlapped with two long separator sheets 70 interposed therebetween and wound in the longitudinal direction. The positive electrode sheet 50 has a configuration in which a positive electrode active material layer 54 is formed along the longitudinal direction on one or both sides (both sides here) of a long positive electrode current collector 52. The negative electrode sheet 60 has a configuration in which a negative electrode active material layer 64 is formed along the longitudinal direction on one or both sides (both sides here) of a long negative electrode current collector 62. The positive electrode active material layer-free portion 52a (i.e., a portion where the positive electrode active material layer 54 is not formed and the positive electrode current collector 52 is exposed) and the negative electrode active material layer-free portion 62a (i.e., a portion where the negative electrode active material layer 64 is not formed and the negative electrode current collector 62 is exposed) are formed so as to protrude outward from both ends in the winding axis direction (i.e., the sheet width direction perpendicular to the longitudinal direction) of the wound electrode body 20. The positive electrode active material layer-free portion 52a and the negative electrode active material layer-free portion 62a are joined to the positive electrode current collector 42a and the negative electrode current collector 44a, respectively.

[0016] The nonaqueous electrolyte 80 usually contains a nonaqueous solvent and a supporting salt (electrolyte salt). As the nonaqueous solvent, various organic solvents such as carbonates, ethers, esters, nitriles, sulfones, and lactones, which are used in electrolytes of general lithium ion secondary batteries, can be used without any particular limitation. Among them, carbonates are preferable, and specific examples thereof include ethylene carbonate (EC), propylene carbonate (PC), diethyl carbonate (DEC), dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), monofluoroethylene carbonate (MFEC), difluoroethylene carbonate (DFEC), monofluoromethyl difluoromethyl carbonate (F-DMC), and trifluorodimethyl carbonate (TFDMC). Such nonaqueous solvents can be used alone or in appropriate combination of two or more.

[0017] As the supporting salt, for example, a lithium salt such as LiPF6 or LiBF4 (preferably LiPF6) can be suitably used. The concentration of the supporting salt is preferably 0.7 mol / L or more and 1.3 mol / L or less.

[0018] In this embodiment, the nonaqueous electrolyte 80 contains an additive (hereinafter also referred to as "additive (A)") which is a Li salt containing at least one of a fluorosulfonyl group and a difluorophosphonyl group. The number of fluorosulfonyl groups and difluorophosphonyl groups contained in the additive (A) is not particularly limited, but is preferably one or two. The number of lithium ions contained in the additive (A) is not particularly limited, but is preferably one.

[0019] Examples of additives (A) include lithium monofluorosulfate, lithium difluorophosphate, lithium bis(fluorosulfonyl)imide, lithium bis(difluorophosphoryl)imide, lithium difluorophosphorylfluorosulfonylimide, and lithium difluorobis(oxalato)phosphate. These can be used alone or in combination of two or more. The action of such additives will be described later.

[0020] The concentration of the additive (A) in the nonaqueous electrolyte 80 is not particularly limited, but if the concentration is too high, the viscosity of the nonaqueous electrolyte 80 may increase, which may lead to an increase in resistance. On the other hand, if the concentration is too low, it may be difficult to obtain the effect of improving the storage characteristics. Therefore, the concentration of the additive (A) in the nonaqueous electrolyte 80 is, for example, 0.1 mass% or more and 3.0 mass% or less, preferably 0.3 mass% or more and 2.0 mass% or less, and more preferably 0.5 mass% or more and 1.5 mass% or less.

[0021] The nonaqueous electrolyte 80 may contain components other than those described above, such as film-forming agents such as vinylene carbonate (VC) and boron-containing oxalato complexes; gas generating agents such as biphenyl (BP) and cyclohexylbenzene (CHB); and thickeners, as long as the effects of the present invention are not significantly impaired.

[0022] The positive electrode current collector 52 constituting the positive electrode sheet 50 may be a known positive electrode current collector used in lithium ion secondary batteries, and examples thereof include a sheet or foil made of a metal having good electrical conductivity (e.g., aluminum, nickel, titanium, stainless steel, etc.). The positive electrode current collector 52 is preferably aluminum foil.

[0023] The dimensions of the positive electrode current collector 52 are not particularly limited and may be appropriately determined depending on the battery design. When an aluminum foil is used as the positive electrode current collector 52, the thickness is not particularly limited, but is, for example, 5 μm or more and 35 μm or less, and preferably 7 μm or more and 20 μm or less.

[0024] The positive electrode active material layer 54 contains a positive electrode active material and carbon nanotubes (CNTs). As the positive electrode active material, a known positive electrode active material used in a lithium ion secondary battery may be used. Specifically, for example, as the positive electrode active material, a lithium composite oxide, a lithium transition metal phosphate compound, or the like may be used. The crystal structure of the positive electrode active material is not particularly limited, and may be a layered structure, a spinel structure, an olivine structure, or the like.

[0025] The lithium composite oxide is preferably a lithium transition metal composite oxide containing at least one of Ni, Co, and Mn as a transition metal element, and specific examples thereof include lithium nickel-based composite oxides, lithium cobalt-based composite oxides, lithium manganese-based composite oxides, lithium nickel manganese-based composite oxides, lithium nickel cobalt manganese-based composite oxides, lithium nickel cobalt aluminum-based composite oxides, and lithium iron nickel manganese-based composite oxides.

[0026] In this specification, the term "lithium nickel cobalt manganese composite oxide" includes oxides containing Li, Ni, Co, Mn, and O as constituent elements, as well as oxides containing one or more additional elements other than those. Examples of such additional elements include transition metal elements and typical metal elements such as Mg, Ca, Al, Ti, V, Cr, Y, Zr, Nb, Mo, Hf, Ta, W, Na, Fe, Zn, and Sn. The additional element may be a semimetal element such as B, C, Si, or P, or a nonmetal element such as S, F, Cl, Br, or I. This also applies to the above-mentioned lithium nickel composite oxide, lithium cobalt composite oxide, lithium manganese composite oxide, lithium nickel manganese composite oxide, lithium nickel cobalt aluminum composite oxide, and lithium iron nickel manganese composite oxide.

[0027] Examples of the lithium transition metal phosphate compound include lithium iron phosphate (LiFePO4), lithium manganese phosphate (LiMnPO4), and lithium manganese iron phosphate.

[0028] These positive electrode active materials may be used alone or in combination of two or more. As the positive electrode active material, lithium nickel cobalt manganese based composite oxide is particularly preferable because of its excellent properties such as initial resistance characteristics.

[0029] The average particle diameter (median diameter: D50) of the positive electrode active material is not particularly limited, but is, for example, 0.05 μm to 25 μm, preferably 1 μm to 20 μm, and more preferably 3 μm to 15 μm. The average particle diameter (D50) of the positive electrode active material can be determined, for example, by a laser diffraction scattering method.

[0030] The content of the positive electrode active material in the positive electrode active material layer 54 (i.e., the content of the positive electrode active material relative to the total mass of the positive electrode active material layer 54) is not particularly limited, but is, for example, 80 mass% or more, preferably 87 mass% or more, more preferably 90 mass% or more, even more preferably 95 mass% or more, and most preferably 97 mass% or more.

[0031] In this embodiment, CNTs are used as the conductive material of the positive electrode active material layer 54. The CNTs are usually dispersed in the form of single particles and / or aggregates together with the positive electrode active material in the positive electrode active material layer 54. The CNTs can improve the conductivity of the positive electrode active material layer 54, and can increase the output of the lithium ion secondary battery 100.

[0032] In this embodiment, CNTs having a G / D ratio of 1.0 to 3.5 as determined by Raman spectroscopy are used. CNTs having such a low G / D ratio are typically obtained by chemical vapor deposition (CVD) without firing, and therefore emit less carbon dioxide during the manufacturing process. Therefore, CNTs having such a low G / D ratio are advantageous in terms of reducing carbon dioxide emissions from the production of materials and components to be used to the completion of the lithium ion secondary battery 100.

[0033] On the other hand, such a low G / D ratio has a large amount of impurities and low crystallinity, and may contain impurities such as metal catalysts, metal catalyst supports, and substrates during CNT production by the CVD method. In this embodiment, CNTs containing Co components are used. The Co components are usually impurities (typically Co catalyst residues) derived from the Co catalyst during CNT production by the CVD method.

[0034] The G / D ratio of the CNTs determined by Raman spectroscopy can be determined according to a known method. Specifically, for example, a Raman spectrum of the CNTs is measured using a known Raman spectroscopic analyzer, and the Raman spectrum is used to determine the G / D ratio at 1590 cm -1 The peak intensity around 1350 cm is the G band intensity. -1 The G / D ratio can be calculated by determining the peak intensities in the vicinity as the D band intensity and calculating the G / D value.

[0035] CNT is typically produced by CVD, but the method for producing CNT is not limited thereto. CNT may be any of single-walled carbon nanotubes (SWCNT), double-walled carbon nanotubes (DWCNT), and multi-walled carbon nanotubes (MWCNT), which may be used alone or in combination of two or more. As CNT, MWCNT is preferred.

[0036] The average length of the CNT is not particularly limited. If the average length of the CNT is too long, the CNT tends to aggregate and the dispersibility tends to decrease. Therefore, the average length of the CNT is preferably 15 μm or less, more preferably 8.0 μm or less, even more preferably 5.0 μm or less, and most preferably 3.0 μm or less. On the other hand, if the average length of the CNT is too short, it tends to be difficult to form a conductive path between the positive electrode active materials. Therefore, the average length of the CNT is preferably 0.3 μm or more, more preferably 0.5 μm or more.

[0037] The average diameter of the CNTs is not particularly limited and is, for example, 0.1 nm to 150 nm, preferably 0.5 nm to 60 nm, and more preferably 0.5 nm to 30 nm.

[0038] The average length and average diameter of CNTs can be obtained, for example, by taking an electron microscope photograph of CNTs and averaging the lengths and diameters of 100 or more CNTs. Specifically, for example, a CNT dispersion is diluted and then dried to prepare a measurement sample. This sample is observed with a scanning electron microscope (SEM) to obtain the lengths and diameters of 100 or more CNTs and calculate the average value. At this time, if the CNTs are re-aggregated, the length and diameter are obtained for the bundle of aggregated CNTs.

[0039] In this embodiment, the amount of Co component in the CNTs in the positive electrode active material layer 54 is 5 ppm by mass to 120 ppm by mass.

[0040] The amount of the Co component of the CNT in the positive electrode active material layer 54 can be obtained, for example, as follows. The mass of the positive electrode active material layer 54 and the content ratio of the CNT in the positive electrode active material layer 54 are obtained according to a known method. The Co content in the CNT is also obtained by a known method (e.g., high-frequency inductively coupled plasma (ICP) emission spectrometry, etc.). Using these values, the amount (ppm by mass) of the Co component of the CNT in the positive electrode active material layer 54 is calculated. Note that CNTs with various Co contents can be manufactured according to a known method and are also available as commercial products. Therefore, the amount of the Co component of the CNT in the positive electrode active material layer 54 can be adjusted by adjusting the Co content in the CNT and / or the content ratio of the CNT in the positive electrode active material layer 54.

[0041] In this way, by using CNTs containing Co and having a G / D ratio of 1.0 to 3.5 as determined by Raman spectroscopy, adjusting the amount of Co in the CNTs in the positive electrode active material layer 54 to 5 ppm by mass to 120 ppm by mass, and further adding additive (A) which is a Li salt containing at least one of a fluorosulfonyl group and a difluorophosphonyl group to the nonaqueous electrolyte, it is possible to impart excellent output characteristics and storage characteristics to a nonaqueous electrolyte secondary battery, even while using CNTs with a low G / D ratio as the conductive material. This is believed to be due to the following reasons.

[0042] According to the study by the present inventor, when CNTs with a low G / D ratio are used as a conductive material for a non-aqueous electrolyte secondary battery, it was found that the reason for the deterioration of storage characteristics is that the Co catalyst remaining in the CNTs dissolves into the non-aqueous electrolyte, and then precipitates at the negative electrode, which promotes the reductive decomposition of the non-aqueous electrolyte. In contrast, when the above-mentioned additive (A) is used, the additive (A) is adsorbed to the surface of the constituent components of the positive electrode by the fluorosulfonyl group and the difluorophosphonyl group. At this time, the additive (A) is also adsorbed to the Co catalyst remaining in the CNTs, which makes it possible to suppress the elution of Co from the CNTs. Therefore, if the amount of Co component of the CNTs in the positive electrode active material layer 54 is 5 ppm by mass to 120 ppm by mass, the deterioration of storage characteristics can be sufficiently suppressed.

[0043] However, if the G / D ratio of the CNT is less than 1.0, the improvement of the storage characteristics is insufficient. In addition, generally, the higher the G / D ratio, the higher the crystallinity of the CNT and the higher the electronic conductivity, which is advantageous for the output characteristics of the non-aqueous electrolyte secondary battery. On the contrary, according to the study by the present inventor, when CNT with a low G / D ratio is used as a conductive material, it was found that the output characteristics of the non-aqueous electrolyte secondary battery are reduced when the G / D ratio becomes large to a certain extent. Therefore, from the viewpoint of the output characteristics of the lithium ion secondary battery 100, the G / D ratio of the CNT is 3.5 or less. The G / D ratio is preferably 1.0 to 3.2, and more preferably 1.0 to 3.0. Furthermore, from the viewpoint of the storage characteristics of the lithium ion secondary battery 100, the G / D ratio is particularly preferably 2.0 to 3.0. From the viewpoint of the output characteristics of the lithium ion secondary battery 100, the G / D ratio is particularly preferably 1.0 to 2.0.

[0044] The amount of Co component in the CNTs in the positive electrode active material layer 54 is preferably 10 ppm by mass to 100 ppm by mass.

[0045] Moreover, if the amount of additive (A) is too large relative to the positive electrode active material, the resistance may increase, and the output characteristics may decrease. Therefore, the amount of additive (A) is preferably 16.0 mg / g or less, more preferably 14.0 mg / g or less, and even more preferably 12.1 mg / g or less, relative to the mass (g) of the positive electrode active material contained in the positive electrode active material layer 54. On the other hand, from the viewpoint of higher storage characteristics, the amount of additive (A) is preferably 0.5 mg / g or more, more preferably 1.5 mg / g or less, and even more preferably 1.9 mg / g or more, relative to the mass (g) of the positive electrode active material contained in the positive electrode active material layer 54.

[0046] In addition to the Co component, the CNT may contain other metal components (for example, components derived from metal catalysts other than Co, catalyst supports, or substrates during the production of CNT by the CVD method) within the range that does not significantly impair the effects of the present invention. Examples of such components include Fe, Al, Mo, and Ti.

[0047] The content of CNT in the positive electrode active material layer 54 is not particularly limited as long as the amount of Co component of the CNT in the positive electrode active material layer 54 is 5 mass ppm to 120 mass ppm. If the content of CNT in the positive electrode active material layer 54 is too large, there is a risk of thickening of the positive electrode slurry during the manufacture of the lithium ion secondary battery 100, a decrease in the impregnation of the nonaqueous electrolyte solution 80 into the positive electrode active material layer 54, and the like. Therefore, the content of CNT in the positive electrode active material layer 54 is, for example, 0.1 mass % or more and 3.0 mass % or less, preferably 0.3 mass % or more and 2.5 mass % or less, and more preferably 0.5 mass % or more and 2.0 mass % or less.

[0048] Typically, only CNTs are used as the conductive material of the positive electrode active material layer 54. However, the positive electrode active material layer 54 may contain a conductive material other than CNTs (e.g., carbon black, etc.) within a range that does not significantly impair the effects of the present invention.

[0049] The positive electrode active material layer 54 may contain components other than the positive electrode active material, such as trilithium phosphate, a binder, a carbon nanotube dispersant (CNT dispersant), etc. As the binder, for example, polyvinylidene fluoride (PVdF) or the like can be used.

[0050] Examples of CNT dispersants that can be used include surfactant-type dispersants (also called low molecular weight dispersants), polymer-type dispersants, and inorganic-type dispersants. The CNT dispersant may be anionic, cationic, amphoteric, or nonionic. Thus, the CNT dispersant may have at least one functional group selected from the group consisting of anionic groups, cationic groups, and nonionic groups in its molecular structure. The surfactant refers to an amphiphilic substance having a chemical structure in which a hydrophilic portion and a lipophilic portion are bonded together by a covalent bond in the molecular structure.

[0051] Specific examples of CNT dispersants include polycondensation aromatic surfactants such as sodium salt of naphthalenesulfonic acid formalin condensate, ammonium salt of naphthalenesulfonic acid formalin condensate, and sodium salt of methylnaphthalenesulfonic acid formalin condensate; polycarboxylic acids and their salts, such as polyacrylic acid and its salts, polymethacrylic acid and its salts; triazine derivative dispersants (preferably containing a carbazolyl group or a benzimidazolyl group); polyvinylpyrrolidone (PVP); polymers having polynuclear aromatics such as pyrene and anthracene in the side chain; polynuclear aromatic ammonium derivatives such as pyrene ammonium derivatives (e.g., compounds in which an ammonium bromide group is introduced into pyrene) and anthracene ammonium derivatives; and the like. These CNT dispersants can be used alone or in combination of two or more. As the CNT dispersant, those containing polynuclear aromatics are preferable. Specifically, as the CNT dispersant, polymers having polynuclear aromatics in the side chain and polynuclear aromatic ammonium derivatives are preferable.

[0052] The content of trilithium phosphate in the positive electrode active material layer 54 is not particularly limited, but is preferably from 1 to 15% by mass, and more preferably from 2 to 12% by mass. The content of the binder in the positive electrode active material layer 54 is not particularly limited, but is preferably from 0.1 to 10% by mass, more preferably from 0.2 to 5% by mass, and even more preferably from 0.3 to 2% by mass.

[0053] The amount of the CNT dispersant may be appropriately determined depending on the type of CNT and CNT dispersant. Here, if the ratio of the CNT dispersant is too small, dispersibility may be insufficient. On the other hand, if the ratio of the CNT dispersant is too large, the CNT dispersant may adhere excessively to the CNT surface, causing an increase in resistance. When the CNT is SWCNT, the amount of the CNT dispersant used is, for example, 1 part by mass to 400 parts by mass, preferably 20 parts by mass to 200 parts by mass, relative to 100 parts by mass of CNT. When the CNT is MWNT, the amount of the CNT dispersant used is, for example, 1 part by mass to 100 parts by mass, preferably 4 parts by mass to 40 parts by mass, relative to 100 parts by mass of CNT.

[0054] The thickness of the positive electrode active material layer 54 is not particularly limited, but is, for example, from 10 μm to 300 μm, and preferably from 20 μm to 200 μm.

[0055] The weight of the positive electrode active material layer 54 is not particularly limited, but is preferably 5 mg / cm per side from the viewpoint of higher output characteristics of the lithium ion secondary battery 100. 2 More than 10 mg / cm is preferable. 2 More preferably, 15 mg / cm 2 The weight of the positive electrode active material layer 54 is more preferably 25 mg / cm. 2 or less than 23 mg / cm 2 It may be the following:

[0056] The positive electrode sheet 50 may contain an insulating layer (not shown) at the boundary between the positive electrode active material layer non-forming portion 52a and the positive electrode active material layer 54. The insulating layer contains, for example, ceramic particles.

[0057] The negative electrode current collector 62 constituting the negative electrode sheet 60 may be a known negative electrode current collector used in lithium ion secondary batteries, and examples thereof include a sheet or foil made of a metal having good electrical conductivity (e.g., copper, nickel, titanium, stainless steel, etc.). Copper foil is preferable as the negative electrode current collector 62.

[0058] The dimensions of the negative electrode current collector 62 are not particularly limited and may be appropriately determined depending on the battery design. When a copper foil is used as the negative electrode current collector 62, the thickness is not particularly limited, but is, for example, 5 μm or more and 35 μm or less, and preferably 6 μm or more and 20 μm or less.

[0059] The negative electrode active material layer 64 contains a negative electrode active material. As the negative electrode active material, for example, a carbon material such as graphite, hard carbon, soft carbon, etc. The graphite may be natural graphite or artificial graphite, or may be amorphous carbon-coated graphite in which graphite is coated with an amorphous carbon material.

[0060] The average particle diameter (median diameter: D50) of the negative electrode active material is not particularly limited, but is, for example, 0.1 μm to 50 μm, preferably 1 μm to 25 μm, and more preferably 5 μm to 20 μm. The average particle diameter (D50) of the negative electrode active material can be determined, for example, by a laser diffraction scattering method.

[0061] The negative electrode active material layer 64 may contain components other than the active material, such as a binder, a thickener, etc. As the binder, for example, styrene butadiene rubber (SBR), polyvinylidene fluoride (PVdF), etc. may be used. As the thickener, for example, carboxymethyl cellulose (CMC), etc. may be used.

[0062] The content of the negative electrode active material in the negative electrode active material layer 64 is preferably 90% by mass or more, and more preferably 95% by mass or more and 99% by mass or less. The content of the binder in the negative electrode active material layer 64 is preferably 0.1% by mass or more and 8% by mass or less, and more preferably 0.5% by mass or more and 3% by mass or less. The content of the thickener in the negative electrode active material layer 64 is preferably 0.3% by mass or more and 3% by mass or less, and more preferably 0.5% by mass or more and 2% by mass or less.

[0063] The thickness of the negative electrode active material layer 64 is not particularly limited, but is, for example, not less than 10 μm and not more than 400 μm, and preferably not less than 20 μm and not more than 300 μm.

[0064] The separator 70 may be a porous sheet (film) made of a resin such as polyethylene (PE), polypropylene (PP), polyester, cellulose, or polyamide. Such a porous sheet may have a single-layer structure or a laminated structure of two or more layers (for example, a three-layer structure in which a PP layer is laminated on both sides of a PE layer). A heat-resistant layer (HRL) containing ceramic particles or the like may be provided on the surface of the separator 70.

[0065] The thickness of the separator 70 is not particularly limited, but is, for example, 5 μm to 50 μm, and preferably 10 μm to 30 μm. The air permeability of the separator 70 obtained by the Gurley test method is not particularly limited, but is preferably 350 sec / 100 cc or less.

[0066] The lithium ion secondary battery 100 constructed as described above has excellent output characteristics and storage characteristics (especially high-temperature storage characteristics). In addition, since CNTs with a small G / D ratio are used, there is no need to produce the CNTs by firing at an extra high temperature, and the amount of carbon dioxide emitted from the production of the materials and members used to the completion of the lithium ion secondary battery 100 is small.

[0067] The lithium ion secondary battery 100 can be used for various purposes. Specific applications include portable power sources for personal computers, portable electronic devices, portable terminals, etc.; power sources for driving vehicles such as electric vehicles (BEVs), hybrid vehicles (HEVs), and plug-in hybrid vehicles (PHEVs); and storage batteries for small power storage devices, among which a power source for driving vehicles is preferred. The lithium ion secondary battery 100 can also be used in the form of a battery pack typically consisting of a plurality of batteries connected in series and / or parallel.

[0068] The above describes, as an example, a rectangular lithium ion secondary battery 100 equipped with a flat wound electrode assembly 20. However, the lithium ion secondary battery can also be configured as a lithium ion secondary battery equipped with a laminated electrode assembly (i.e., an electrode assembly in which multiple positive electrodes and multiple negative electrodes are alternately laminated). The lithium ion secondary battery can also be configured as a cylindrical lithium ion secondary battery, a laminated case type lithium ion secondary battery, etc.

[0069] The secondary battery according to this embodiment can be constructed as a non-aqueous electrolyte secondary battery other than a lithium ion secondary battery in accordance with a known method.

[0070] Examples of the present invention will be described in detail below, but it is not intended that the present invention be limited to those shown in these examples.

[0071] [Examples 1 to 5 and Comparative Examples 1 to 11] LiNi as a positive electrode active material 1 / 3 Co 1 / 3 Mn 1 / 3O2, a conductive material, and PVdF as a binder were mixed in a mass ratio of active material:conductive material:PVdF=98.5:1.0:0.5. MWCNT (average diameter 10 nm, average length 0.5 μm) was used as the conductive material. Eight types of MWCNT with different Co content and / or G / D ratio were used. Table 1 shows the Co content (ppm by mass) of MWCNT in the positive electrode active material layer and the G / D ratio of MWCNT in each example and each comparative example. The Co content in MWCNT and the G / D ratio of MWCNT were measured by the method described below.

[0072] An appropriate amount of N-methyl-2-pyrrolidone was added to the mixture to prepare a positive electrode slurry. The positive electrode slurry was applied to both sides of an aluminum foil having a thickness of 12 μm as a positive electrode current collector. At this time, a positive electrode slurry uncoated portion was provided on the aluminum foil as a lead connection portion. The amount of the positive electrode slurry applied was set so that the basis weight of the positive electrode active material layer formed was 10.0 mg / cm2 in total on both sides. 2 It was adjusted so that

[0073] The applied slurry was dried to form a positive electrode active material layer. The obtained sheet was pressed with a roller and then cut to a predetermined size to obtain a positive electrode having a positive electrode active material layer formed on both sides of the positive electrode current collector. The packing density of the positive electrode active material layer was 2.40 g / cm. 3 It was.

[0074] Graphite as a carbon-based negative electrode active material, sodium salt of carboxymethylcellulose (CMC-Na), and a dispersion of styrene butadiene rubber (SBR) were mixed in a solid mass ratio of graphite:CMC-Na:CMC=98.0:1.0:1.0. An appropriate amount of ion-exchanged water was further added to prepare a negative electrode slurry. The negative electrode slurry was applied to both sides of a copper foil with a thickness of 8 μm as a negative electrode current collector. At this time, a negative electrode slurry uncoated portion was provided on the copper foil as a lead connection portion.

[0075] The applied paste was dried to form a negative electrode active material layer. The obtained sheet was pressed with a roller and then cut to a predetermined size to obtain a negative electrode in which a negative electrode active material layer was formed on both sides of the negative electrode current collector. The packing density of the negative electrode active material layer was 1.35 g / cm. 3 It was.

[0076] A lead was attached to each of the positive and negative electrodes prepared above. A single-layer polypropylene separator was prepared. The positive and negative electrodes were alternately stacked one by one with the separators interposed therebetween to prepare a laminated electrode body.

[0077] A mixed solvent containing ethylene carbonate (EC), dimethyl carbonate (DMC), and ethyl methyl carbonate (EMC) in a volume ratio of 30:40:30 was prepared. In Comparative Examples 1 to 8, lithium bis(oxalate)borate was dissolved in this mixed solvent at a concentration of 0.8 mass%, and LiPF6 as a supporting salt was dissolved at a concentration of 1.15 mol / L. In Examples 1 to 5 and Comparative Examples 9 to 11, lithium bis(oxalate)borate was dissolved in this mixed solvent at a concentration of 0.8 mass%, lithium fluorosulfate was dissolved as an additive (A1) at a concentration of 1.0 mass%, and LiPF6 as a supporting salt was dissolved at a concentration of 1.15 mol / L. In this manner, a nonaqueous electrolyte was obtained. In Examples 1 to 5 and Comparative Examples 9 to 11, the mass ratio of the additive (A1) to the positive electrode active material used was 12.1 mg / g.

[0078] The laminated electrode body prepared above and a non-aqueous electrolyte solution were housed in a square battery case and sealed to obtain a square lithium ion secondary battery for evaluation.

[0079] <Raman spectroscopy> Using a laser Raman microscope "RAMANwalk" (manufactured by Nanophoton Co., Ltd.), Raman images of the surface of the positive electrode active material layer of the positive electrode used in each Example and Comparative Example were obtained, and the portion where the conductive material (CNT) was present was identified. Next, the Raman spectrum of the conductive material (CNT) portion was measured. -1 The peak intensity around 1350 cm is the G band intensity.-1 The peak intensities in the vicinity were determined as the D-band intensities, respectively, and the G / D ratio was calculated.

[0080] <ICP Spectroscopic Analysis of CNT> ICP emission spectroscopic analysis was performed on the CNTs used in each example and comparative example to determine the Co content. Based on this Co content, the amount of the Co component of the CNTs in the positive electrode active material layer was calculated for each example and each comparative example.

[0081] <Output Evaluation> Each evaluation lithium-ion secondary battery was adjusted to 50% SOC (State of charge) by constant current-constant voltage (CC-CV) charging and then placed in an environment at 25°C. Discharge was performed at a current value of 5C for 10 seconds, and the voltage rise amount ΔV at this time was obtained. Using this voltage rise amount ΔV and the current value, the initial output resistance value of each evaluation lithium-ion secondary battery was calculated. The results are shown in Table 1.

[0082] <High Temperature Storage Characteristics Evaluation> Each evaluation lithium-ion secondary battery was placed in an environment at 25°C, and CC-CV charging was performed at a charging voltage of 4.2V and a charging current of 0.5C for 3 hours. Then, constant current (CC) discharge was performed at a discharge current of 0.5C until 3.0V. The discharge capacity at this time was measured and used as the initial capacity.

[0083] Next, each evaluation lithium-ion secondary battery was placed in an environment at 25°C, and CC-CV charging was performed at a charging voltage of 4.2V and a charging current of 0.5C for 3 hours. Then, each evaluation lithium-ion secondary battery was stored in a high-temperature bath at 60°C for 100 days, and the discharge capacity was measured in the same manner as the initial capacity. The capacity retention rate (%) was calculated from (discharge capacity after storage / initial capacity) × 100. The results are shown in Table 1.

[0084]

Table 1

[0085] As the results in Table 1 show, by setting the G / D ratio of the CNT within the range of 1.0 to 3.5, setting the amount of Co component of the CNT in the positive electrode active material layer within the range of 5 mass ppm to 120 mass ppm, and adding additive (A1), which is a Li salt having a fluorosulfonyl group, to the non-aqueous electrolyte, the capacity retention rate after high-temperature storage is high and the initial output resistance is also sufficiently small.

[0086] [Examples 6 to 15 and Comparative Examples 12 to 17] In Examples 6 to 15 and Comparative Examples 12 to 17, the coating amount of the positive electrode slurry was set so that the basis weight of the positive electrode active material layer formed was 46.0 mg / cm2 in total on both sides. 2 The packing density of the positive electrode active material layer was adjusted to 3.60 g / cm 3 In Examples 6 to 10 and Comparative Examples 12 to 14, lithium bis(oxalate)borate was dissolved in the mixed solvent at a concentration of 0.8 mass%, lithium fluorosulfate was dissolved as the additive (A1) at a concentration of 0.5 mass%, and LiPF6 was dissolved as the supporting salt at a concentration of 1.15 mol / L. As a result, the mass ratio of the additive (A1) to the positive electrode active material used was changed to 1.9 mg / g. In Examples 11 to 15 and Comparative Examples 15 to 17, lithium bis(oxalate)borate was dissolved in the mixed solvent at a concentration of 0.8 mass%, lithium fluorosulfate was dissolved as the additive (A1) at a concentration of 1.5 mass%, and LiPF6 was dissolved as the supporting salt at a concentration of 1.15 mol / L. As a result, the mass ratio of the additive (A1) to the positive electrode active material used was changed to 5.7 mg / g. Except for the above, a lithium ion secondary battery for evaluation was produced and evaluated in the same manner as above. The results are shown in Table 2.

[0087] [Table 2]

[0088] As shown by the results in Table 2, even when the amount of additive (A1) was changed, when the G / D ratio of the CNT was within the range of 1.0 to 3.5 and the amount of the Co component of the CNT in the positive electrode active material layer was within the range of 5 ppm by mass to 120 ppm by mass, the capacity retention rate after high-temperature storage was high and the output resistance was sufficiently small.

[0089] [Examples 16 to 30 and Comparative Examples 18 to 26] In Examples 16 to 30 and Comparative Examples 18 to 26, the coating amount of the positive electrode slurry was set so that the basis weight of the positive electrode active material layer formed was 46.0 mg / cm2 in total on both sides. 2 The packing density of the positive electrode active material layer was adjusted to 3.60 g / cm 3 In Examples 16 to 20 and Comparative Examples 18 to 20, lithium bis(oxalate)borate was dissolved in the above mixed solvent at a concentration of 0.8% by mass, lithium difluorosulfonate was dissolved as the additive (A2) at a concentration of 1.5% by mass, and LiPF6 was dissolved as the supporting salt at a concentration of 1.15 mol / L. In Examples 21 to 25 and Comparative Examples 21 to 23, lithium bis(oxalate)borate was dissolved in the above mixed solvent at a concentration of 0.8% by mass, lithium difluorophosphoryl fluorosulfonylimide was dissolved as the additive (A3) at a concentration of 1.5% by mass, and LiPF6 was dissolved as the supporting salt at a concentration of 1.15 mol / L. In Examples 26 to 30 and Comparative Examples 24 to 26, lithium bis(oxalato)borate was dissolved in the mixed solvent at a concentration of 0.8% by mass, lithium difluorobis(oxalato)phosphate was dissolved as additive (A4) at a concentration of 1.5% by mass, and LiPF6 was dissolved as a supporting salt at a concentration of 1.15 mol / L. As a result, in Examples 16 to 30 and Comparative Examples 18 to 26, the mass ratio of the additive to the positive electrode active material used was changed to 5.7 mg / g. Except for the above points, lithium ion secondary batteries for evaluation were produced and evaluated in the same manner as above. The results are shown in Table 3. The chemical structures of the additives (A2) to (A4) used are shown below together with the chemical structure of additive (A1).

[0090] [ka]

[0091] [Table 3]

[0092] As shown in the results of Table 3, even when the type of additive was changed, the same tendency as with additive (A1) was obtained. Additives (A1) to (A4) are Li salts containing at least one of a fluorosulfonyl group and a difluorophosphonyl group. Therefore, according to the nonaqueous electrolyte secondary battery disclosed herein, it is possible to provide a nonaqueous electrolyte secondary battery that has excellent output characteristics and storage characteristics while using CNTs with a low G / D ratio as a conductive material.

[0093] Although the specific examples of the present invention have been described in detail above, these are merely examples and do not limit the scope of the claims. The technology described in the claims includes various modifications and changes of the specific examples exemplified above.

[0094] That is, the nonaqueous electrolyte secondary battery disclosed herein has the following features [1] to [6]. [1] A nonaqueous electrolyte secondary battery comprising a positive electrode, a negative electrode, and a nonaqueous electrolyte, The positive electrode includes a positive electrode current collector and a positive electrode active material layer, The positive electrode active material layer contains a positive electrode active material and carbon nanotubes, The carbon nanotubes contain a Co component, The carbon nanotubes have a G / D ratio of 1.0 to 3.5 as determined by Raman spectroscopic analysis; the amount of Co component of the carbon nanotubes in the positive electrode active material layer is 5 ppm by mass to 120 ppm by mass; The non-aqueous electrolyte contains an additive which is a Li salt containing at least one of a fluorosulfonyl group and a difluorophosphonyl group. Nonaqueous electrolyte secondary battery. [2] The nonaqueous electrolyte secondary battery according to item [1], wherein a ratio of an amount (mg) of the additive to a mass (g) of the positive electrode active material contained in the positive electrode active material layer is 0.5 mg / g to 16.0 mg / g. [3] The nonaqueous electrolyte secondary battery according to item [1] or [2], wherein the additive is at least one selected from the group consisting of lithium monofluorosulfate, lithium difluorophosphate, lithium bis(fluorosulfonyl)imide, lithium bis(difluorophosphoryl)imide, lithium difluorophosphoryl fluorosulfonyl imide, and lithium difluorobis(oxalato)phosphate. [4] The nonaqueous electrolyte secondary battery according to any one of items [1] to [3], wherein the carbon nanotubes have a G / D ratio of 1.0 to 3.0 as determined by Raman spectroscopic analysis. [5] The nonaqueous electrolyte secondary battery according to any one of items [1] to [4], wherein the amount of Co component of the carbon nanotubes in the positive electrode active material layer is 10 ppm by mass to 100 ppm by mass. [6] The weight of the positive electrode active material layer on one side is 5 mg / cm 2 ~25mg / cm 2 The nonaqueous electrolyte secondary battery according to any one of items [1] to [5], [Explanation of symbols]

[0095] 20 Wound electrode body 30 Battery case 36 Safety valve 42 Positive terminal 42a Positive current collector 44 Negative terminal 44a Negative current collector plate 50 Positive electrode sheet (positive electrode) 52 Positive electrode current collector 52a Portion where positive electrode active material layer is not formed 54 Cathode active material layer 60 Negative electrode sheet (negative electrode) 62 Negative electrode current collector 62a Part where negative electrode active material layer is not formed 64 Negative electrode active material layer 70 Separator sheet (separator) 80 Nonaqueous electrolyte 100 Lithium-ion secondary battery

Claims

1. A non-aqueous electrolyte secondary battery comprising a positive electrode, a negative electrode, and a non-aqueous electrolyte, The positive electrode includes a positive electrode current collector and a positive electrode active material layer, The positive electrode active material layer contains a positive electrode active material and carbon nanotubes, The carbon nanotubes contain a Co component, The carbon nanotubes have a G / D ratio of 1.0 to 3.5 as determined by Raman spectroscopy; the amount of Co component of the carbon nanotubes in the positive electrode active material layer is 5 ppm by mass to 120 ppm by mass; The non-aqueous electrolyte contains an additive which is a Li salt containing at least one of a fluorosulfonyl group and a difluorophosphonyl group. Nonaqueous electrolyte secondary battery.

2. 2. The nonaqueous electrolyte secondary battery according to claim 1, wherein a ratio of an amount (mg) of the additive to a mass (g) of the positive electrode active material contained in the positive electrode active material layer is 0.5 mg / g to 16.0 mg / g.

3. 2. The nonaqueous electrolyte secondary battery according to claim 1, wherein the additive is at least one selected from the group consisting of lithium monofluorosulfate, lithium difluorophosphate, lithium bis(fluorosulfonyl)imide, lithium bis(difluorophosphoryl)imide, lithium difluorophosphorylfluorosulfonylimide, and lithium difluorobis(oxalato)phosphate.

4. 2. The nonaqueous electrolyte secondary battery according to claim 1, wherein the carbon nanotubes have a G / D ratio of 1.0 to 3.0 as determined by Raman spectroscopic analysis.

5. 2. The nonaqueous electrolyte secondary battery according to claim 1, wherein the amount of Co component of the carbon nanotubes in the positive electrode active material layer is 10 ppm by mass to 100 ppm by mass.

6. The weight per surface of the positive electrode active material layer is 5 mg / cm 2 ~25mg / cm 2 2. The nonaqueous electrolyte secondary battery according to claim 1,